Respuesta :

Answer: (-3, -5)

Step-by-step explanation:

-6x +  y =  13  

6x + 3y = -33

         4y = -20

        ÷4     ÷4

          y  =  -5

6x + 3y = -33

6x + 3(-5) = -33

6x - 15 = -33

6x        = -18

x         = -3

*********************************************************************************

Answer: ([tex]\frac{1}{3}[/tex], 2)

Step-by-step explanation:

9x +  y =  5   →    1(9x +  y =  5)   →    9x +  y =  5

3x - 3y = -5   →  -3(3x - 3y = -5)  →   -9x + 9y = 15

                                                                10y = 20

                                                              ÷10    ÷10

                                                                   y = 2

9x +  y =  5

9x + (2) = 5

9x        = 3

 x         = [tex]\frac{1}{3}[/tex]